Taiwan Society of Colon and Rectum Surgeons (TSCRS) Consensus for Anti-Inflammatory Nutritional Intervention in Colorectal Cancer - Ma, Cheng-Jen; Hu, Wan-Hsiang; Huang, Meng-Chuan; Chiang, Jy-Ming; Hsieh, Pao-Shiu; Wang, Huann-Sheng; Chiang, Chien-Ling; Hsieh, Hui-Min; Chen, Chou-Chen; Wang, Jaw-Yuan (Frontiers in Oncology, 2022)
Malnutrition and systemic inflammatory response (SIR) frequently occur in patients with colorectal cancer (CRC) and are associated with poor prognosis. Anti-inflammatory nutritional intervention is not only a way to restore the malnourished status but also modulate SIR. Nine experts, including colorectal surgeons, physicians and dieticians from 5 hospitals geographically distributed in Taiwan, attended the consensus meeting in Taiwan Society of Colon and Rectum Surgeons for a 3-round discussion and achieved the consensus based on a systematic literature review of clinical studies and published guidelines. The consensus recommends that assessment of nutritional risk and SIR should be performed before and after CRC treatment and appropriate nutritional and/or anti-inflammatory intervention should be adapted and provided accordingly.